RELIGION AND POLITICAL ECONOMY - Adlan, Muhamad Aqim (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2023)
This article seeks to investigate the integration between political economy and religion offered in the forum Religion of Twenty (R20). The idea of R20 forum by Nahdlatul Ulama (NU) is one of the ideas to unite perceptions between countries and religions. It is based on the phenomenon of the global economy which has begun to be disrupted by conflicts and wars in several countries. Various wars by the superpowers have had implications for disrupting economic stability. Thus, the role of religion in terms of world peace also contributes to the success of global economic stability. In further analysis, this article refers to Ibn Khaldun, Al-Ghazali, Adam Smith, David Ricardo, and John Stuart Mill’s political economy to answer how is the relationship between religion and world peace in economic development? And what role does the R20 forum play in integrating political economy and religion for global economic development? The findings in this article indicate that the sources of political economy in R20 are a means of integrating its patterns in line with the values and essence of religious teachings.